Chromosome‐level genome assembly of the endangered humphead wrasse Cheilinus undulatus: Insight into the expansion of opsin genes in fishes. (9th July 2021) - Liu, Dong; Wang, Xinyang; Guo, Hongyi; Zhang, Xuguang; Zhang, Ming; Tang, Wenqiao
Abstract: Wrasses are dominant components of major coral reef systems. Among wrasses, Cheilinus undulatus is an endangered species with high economic and ecological value that exhibits sex reversal of females to males, while sexual selection occurs in breeding aggregations. However, the molecular‐associated mechanism underlying this remains unclear. Opsin gene diversification is regarded as a potent force in sexual selection. Here we present a genome assembly of C . undulatus, using Illumina, Nanopore and Hi‐C sequencing. The 1.17 Gb genome was generated from 328 contigs with an N50 length of 16.5 Mb and anchored to 24 chromosomes. In total, 22, 218 genes were functionally annotated, and 96.36% of BUSCO genes were fully represented. Transcriptomic analyses showed that 96.79% of the predicted genes were expressed. Transposons were most abundant, accounting for 39.88% of the genome, with low divergence, owing to their evolution with close species ~60.53 million years ago. In total, 567/1, 826 gene families were expanded and contracted in the reconstructed phylogeny, respectively. Forty‐six genes were under positive selection. Comparative genomic analyses with other fish revealed expansion of opsin SWS2B, LWS1 and Rh2 . The elevated duplicates of SWS2B were generated by gene conversions via transposition of transposons followed by nonallelic homologous recombination. Amino acid substitutions of opsin paralogues occurred at key tuning sites, causing a spectral shift in maximal absorbance of visual pigment to capture functional changes. Among these opsin genes, SWS2B ‐ 3 and 4 and Rh1 are expressed in the retina. The genome sequence of C . undulatus provides valuable resources for future investigation of the conservation, evolution and behaviour of fishes.